Trabalho: vilão ou salvação? Sofrimento psíquico e alcoolismo entre servidores técnico-administrativos da Universidade Federal do Ceará - Holanda, Sylvana Gomes (2007)
Alcoholism has affected from 10% to 15% of the Brazilian workers and also has been a problem identified into the public service. We have in view with this study to investigate the alcoholism phenomenon among the technician-administrative employees of the Federal University of Ceará, searching to establish interfaces between the chemical dependence, the work and the psychic suffering. In order to reach the target of the analysis, we identified a group of 52 servers that was carried through as chemical dependents amongst a group of servers attended for the orientation service of the Human Resources Department of the University in the last ten years. Among they we selected five servers to be interviewed. Half-directed individual interviews with open questions had been carried through, broaching themes like: family history, acquisition of the chemical vice, admittance in the public enterprise, conditions of work, the sense attributed to the carried through tasks, relationship with their chiefs, etc. The material was transcribed and submitted to analyzes of its content, that determined some category-synthesis to guide the discussion of the proposal problem. The results disclose that these public servers, in most, have alcoholism history into family and they already presented this problem before the admittance in the public service. From one side they consider the job as a source of survival and a safe port, in scenery of precarious work and scarcity of the job. On the other hand, the work is also identified as cause of suffering for being empty of meaning, acting as co-operator in the maintenance of the chemical dependence. However, the fact of four of these servers to stand aside of the alcohol thanks to psychosocial support and also to the change for an activity that permits them to be recognized as qualified workers, makes believe that the work, when endowed with positive direction for the worker, it also acts as an important co-operator in the recuperation and in the maintenance of the sobriety.